The Effectiveness of a Walking Booster Program for Seniors - Jancey, Jonine; Lee, Andy; Howat, Peter; Burke, Linda; Leong, C.; Shilton, Trevor (American Journal of Health Promotion, Inc., 2011)
Purpose: To determine the effectiveness of a 3-month home-based booster program for seniors to increase walking. Design: A longitudinal prospective study. Setting: Perth, Western Australia. Subjects: Of the 177 (of 260) program participants and 236 (of 313) controls who initially completed the neighborhood walking intervention, 114 (64%) and 134 (57%) were available for the booster, and 100 and 131 participants completed the entire program, respectively. Intervention: A 6-month neighborhood walking intervention was followed 12 months later by a 3-month home-based booster program comprised of print-based materials, a pedometer, and two motivational phone calls. Measures: A self-reported questionnaire was administered at four time points: original intervention, baseline (t1) and 6 months (t2); booster, 18 months (t3) and 21 months (t4). Physical activity levels were measured using the International Physical Activity Questionnaire. Personal and demographic information was collected.Analysis: Descriptive statistics and repeated-measures analysis of variance. Results: The intervention group's mean time spent walking for recreation and mean time spent walking for errands per week showed significant increases between t1 and t2, but the weekly mean time walking for recreation dropped by 52 minutes from t2 to t3. Significant increases were evident from t3 to t4 as a result of the booster. Walking levels for the control group remained stable over the study period. Conclusion: Physical activity levels of seniors revert once an intervention concludes. A home-based booster program can reactivate physical activity levels. Hence, program planners should include booster sessions for program sustainability.